Testing the ability of selected financial ratios in tracking the out performance of stocks for the hotel and property sectors - Kok, Hwee Ping (2015)
This study attempts to investigate the ability of financial ratios to track outperforming stocks. Four historical financial ratios (PIE, P/BV, ROE and ROA) and the widely used prospective PIE ratio were used to track outperforming stocks. The study will undergo two levels of analysis. Within the first level of analysis, we used each of the historical financial ratios to track outperforming stocks both on a one-year and two-year basis. In determining outperformance, we examined how well the prices of stocks performed when compared to that of an industry average return . In our analysis, we sought to discover if the use of simple historical financial ratios was able to provide a means of outperforming the industry average using a one-year and a two-year time frame . If such opportunities existed, then the market may be deemed inefficient in the semistrong form . For the second level of analysis, prospective P/E ratio was used to review outperformance. In this analysis, we used the price in year zero against the earnings in year one (for the one-year period analysis) with the assumption that some degree of forecasting accuracy is attainable. That is, given that a few investment professionals and investors were accurate in their forecast given the accessibility to insider information, would be able to earn abnormal profits. At this level, we reviewed the usefulness of accurate forecast in identifying stocks that would show outperformance against the industry on a one-year and two-year basis. Last but not least, discussions on the empirical findings were presented in Chapter five with special mention being made on the usefulness of ratio analysis as well as the form of market efficiency applicable to the Singapore's Hotel and Property sectors as suggested from the findings in this study.